EFFECTS OF LONG-TERM AND HIGH-DENSITY NET-PEN CAPTIVITY ON MEAT QUALITY, NUTRITIONAL COMPOSITION OF WILD-CAUGHT BIGHEAD CARP (Hypophthalmichthys nobilis) - Yangxin Dai; Nan Xie; Yulai Dai; Wei Guo; Jiayong Pan; Jianqiang Shao; Yuxi Wang (Journal of Animal and Plant Sciences, 2024)
This study investigates the impact of temporary net-pen captivity on the fresh meat quality and nutritional composition of wild bighead carp (Hypophthalmichthys nobilis) caught from Qiandao Lake over an 18-week experimental period. The research aimed to assess changes in body size, muscle texture, and the nutritional profile of the fish during captivity, which are critical factors for the freshwater fishery industry. The research methodology encompassed biometric measurements, texture profile analysis, and assessments of the muscle's nutritional profile, including protein and fatty acid content. Results indicate significant alterations in the body size and nutritional composition of bighead carp, with notable effects on the muscle texture, potentially affecting the meat's taste and chewiness. Variations in protein and fatty acid content were observed, likely influenced by physical activity restrictions, feed limitations, and water quality changes during captivity. The study concludes that temporary net-pen captivity significantly impacts the meat quality and nutritional value of bighead carp, with implications for sustainable fisheries management. It is recommended that the captivity period for wild bighead carp be curtailed to within 3 weeks, extending to a maximum of 12 weeks to ensure product quality. These findings are essential for guiding the freshwater fishery industry towards sustainable practices that balance the health of the fish and the quality of the final product.
Keywords: bighead carp Hypophthalmichthys nobilis; wild-caught; temporary net-pen captivity; fresh meat quality; nutritional composition